The population of Solenopsis sp. (Hymenoptera: Formicidae) in four condition of rice Held embankment. Issue 2 (July 2021) - Abdullah, T; Gassa, A; Aminah, S N; Annisaa, N W
Abstract: Fire red ants ( Solenopsis sp.) as the predators often found in rice fields. Although many farmers not yet know well this potential insects, in Philippines, this adaptive predator has been used to control golden apple snail with satisfying results. In a period of two days, predatory ants able destroyed 50% the eggs of golden apple snail Pomacea canaliculata attached to the leaves of rice plants. The purpose of the research is to study the effect of characteristic differences vegetation of rice field bund to the diversity of ants in the habitat. Research data collection was conducted in Manggala district, Makassar. Identification and observation of ants species was held at the Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Hasanuddin University, Makassar. The research was held from March to May 2018. The results was showed that the bund contain banana tree vegetation had the highest Solenopsis sp. population with 288 individuals. The lowest on the embankment with broad leaf vegetation only 29 individuals. The highest number of individual ants was found in Solenopsis sp. with 353 individuals, then the lowest is Tetramorium sp. with 2 individuals. The difference conditions of vegetation bund showed greatly affects in the number of ants due to differences in the conditions needs of each ant species for their suitable habitat.